Latino entrepreneurs and social media adoption: personal and business social network platforms. Issue 4 (15th April 2019) - Gavino, Monica C.; Williams, Denise E.; Jacobson, David; Smith, Iris
Abstract : Purpose: The purpose of this paper is to examine both the Latino/Hispanic entrepreneurs' social media adoption (SMA) for business purposes and the influence of culture on personal versus business social network platform (SNP) selection. Design/methodology/approach: The Technology Acceptance Model's (TAM) factors of perceived usefulness (PU) and perceived ease of use (PEU) as drivers of Latino/Hispanic entrepreneurs' social network platform selection are examined as well as the effect of SMA on revenue. Data was collected from 633 small business owners across the United States via an online survey administered in English and Spanish. Findings: Results indicate that Latino/Hispanic business owners use personal SNP more than business SNP for business purposes. PU and PEU were not found to predict personal SNP for Latino/Hispanic entrepreneurs. However, for Non-Latino/Hispanics, PU was significant while PEU was marginally significant. Findings for PU and PEU as predictors of business SNP indicate similar results for both Latino/Hispanic and non-Latino/Hispanic entrepreneurs, where only PEU was significant. Finally, there was no relationship between either business or personal SNP and revenue for either Latino/Hispanic or non-Latino/Hispanic entrepreneurs. Practical implications: This research provides more insight into Latino/Hispanic entrepreneurs' self-directed engagement in personal SNP (Facebook) and business SNP (LinkedIn) for business purposes and invites future research in this population to further examine cultural influence and business performance. The findings support the need for Latino/Hispanic entrepreneurs' strengthening their competency in social media usage to remain competitive, as doing so will enhance their capability for building customer relationships, brand development, and equity financing. Originality/value: This investigation 1) examines SMA's role in Latino/Hispanic small and medium enterprises (SMEs); 2) distinguishes between personal and business social network platforms; 3) investigates TAM's relevance for Latino/Hispanic entrepreneurs' use of social media for business; and 4) explores SME social media usage as a predictor of revenue. We seek to provide practitioners with a greater understanding of how they may influence business success and sustainability through better competency development and usage of social media platforms.